Test of arbitrage pricing theory on the Tehran stock exchange: the case of a shariah-compliant close economy - Sabetfar, Pooya; Cheng, Fan Fah; Ramadilli Mohd, Shamsher Mohamad; Amin Noordin, Bany Ariffin (Canadian Center of Science and Education, 2011)
This paper provides weak evidence in support for the application of Arbitrage Pricing Theory (APT) on the Iranian stock market in the Sharia is the sacred law of Islam faith.) based close economy. Tests conducted using the principal component analysis and canonical correlation model showed that at least one to three factors that can explain the cross-section of expected returns in this market. Financial and economical sanctions possibly explain the negative stock market returns which reflect the reaction of investors to the announcement of sanctions. Overall, the results suggest that there are four groups of macroeconomic variables in the test period that affect stock returns for the test period, 1991 to 2008, but the significance of these factors is not consistent over time. In general the findings document a weak applicability of APT in this market.